Tác động của trách nhiệm xã hội của doanh nghiệp đến sự gắn kết của nhân viên: Nghiên cứu tại các doanh nghiệp công nghệ thông tin và truyền thông tại Hà Nội - Nguyễn Duy , Thành; Đào Đức , Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Based on the view of Social Exchange Theory, this research analyzes the impact of corporate social responsibility on the characteristics of employees on their engagement. The research applied Structural Equation Modeling with both unidimensional and multidimensional analysis to process the data of 453 employees working for Information & Communication Technology (ICT) enterprises in Hanoi. The results indicate that corporate social responsibility has a positive impact on employee engagement, in addition, legal responsibility has the strongest impact. The research also used control variables such as gender and job tenure. The results only show that job tenure has an effect on employee engagement.